Discourses : Conversations in Postmodern Art and Culture - Adamson, Walter; Akomfrah, John; Anderson, Laurie; Ando, Tadao; Attille, Martina; Auguiste, Reece; Barthes, Roland; Bartlett, Neil; Bell, Arthur; Beuys, Joseph; Birnbaum, Dara; Blumenthal, Lyn; et al. (New York : New Museum of Contemporary Art, 1990)
Anderson, Laurie ; Ando, Tadao ; Beuys, Joseph ; Birnbaum, Dara ; Black Audio Film Collective ; Blumenthal, Lyn ; Borofsky, Jonathan ; Boyle, Jimmy ; Burgee, John ; Eichelberger, Ethyl ; Fury, Gran ; Hammons, David ; Johnson, Philip ; Krier, Leon ; McLaren, Malcolm ; Rollins, Tim ; Savage, Lily ; Thornton, Leslie Tillotson ; Wodiczko, Krzysztof
Engels
boek